SOCIOECONOMIC-EPIDEMIOLOGIC FACTORS AND THEIR RELATIONSHIPWITH THE SEROPREVALENCE OF TOXOPLASMOSIS IN ASSISTED PREGNANTWOMEN IN “FELIPE ARRIOLA IGLESIAS” AND “CESAR GARARAY GARCIA” HOSPITAL, IQUITOS, PERU, 2009 - Reátegui B., Carmen (2011)
The relation between socioeconomic-epidemiologic factors and seroprevalence of Toxoplasmosis in pregnant women at the Hospital "Felipe Arriola" and "Cesar Garayar" in the Iquitos city Peru in 2009 was determined. The study was cross sectional in 355 pregnant women aged 15 to 45 years of age who attended pre-natal control, intentionally selected. We applied a socio-epidemiological survey on personal, economic, health, housing, co-habitation with cats and other animals, and eating habits. IgG and IgM antibodies to Toxoplasma gondii using a commercial ELISA kit were determined, for statistical analysis test was used Mantel-Heanszel X2. The overall seroprevalence of toxoplasmosis was 97.6% in pregnant women in the Hospital "Felipe Arriola" and 97.4% in the Hospital "Cesar Garayar"; the frequency of IgG antibodies was 94.5% and 86.8% in pregnant women in Hospitals "Felipe Arriola" and "Cesar Garayar", respectively. There were low frequencies of IgG and IgM, 3.1% in the Hospital "Felipe Arriola" and 10.5% in Hospital “Cesar Garayar”. Socio-epidemiological factors significantly associated with the seroprevalence of toxoplasmosis were: intake of fruits and vegetables without washing (p = 0.002) in pregnant women in the Hospital "Felipe Arriola", live in rustic home (p = 0.010) and cohabitation with other animals (p = 0.02) in pregnant women Hospital “Cesar Garayar". We conclude that seroprevalence of toxoplasmosis in pregnant women was high in both hospitals, Iquitos, Peru, 2009.